Impact of climate change adaptation on food security in Ukambani Region, Kenya - Amos Otieno Wanjara; Paul Okeyo Ogembo (Indonesian Journal of Applied Environmental Studies, 2026)
Ukambani region falls  in the Arid and Semi-Arid Lands (ASALs) in Kenya. Given the scenario, climate change adaptation strategies would become handy in alleviating food insecurity. The purpose of the study was to Evaluate the impact of climate change adaptation on food security in Ukambani. Specific objectives were to determine the climate change adaptation strategies used in Ukambani Region, to determine the effects of the climate change adaptation strategies on food production,  and to determine the way forward on climate change adaptation strategies towards sustainable food security assurance in Ukambani Region. The study established that there are climate change adaptation strategies that have either impacted on food security in the region negatively or positively. Based on the study findings, it is becoming apparent that certain strategies were sustainable while others like burning charcoal as an alternative sources of livelihood and looking for government’s /NGOs relief food support may not be sustainable. The findings have implications on the stakeholders and policy maker’s interventions towards sustainable climate change adaptation strategies for sustainable food security.